2014
DOI: 10.1111/cgf.12393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of User Characteristics and Different Layouts on an Interactive Visualization for Decision Making

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 39 publications
2
66
0
1
Order By: Relevance
“…Gaze data has also been investigated to predict long-term user traits (e.g., perceptual speed, visual working memory, verbal working memory, locus of control), as well as task type and task completion time [13,17,41]. Past studies have shown that user characteristics themselves (e.g., cognitive abilities, personality traits) can predict how well a user will perform on, or prefer, a given information visualization system [13,17,23,41].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Gaze data has also been investigated to predict long-term user traits (e.g., perceptual speed, visual working memory, verbal working memory, locus of control), as well as task type and task completion time [13,17,41]. Past studies have shown that user characteristics themselves (e.g., cognitive abilities, personality traits) can predict how well a user will perform on, or prefer, a given information visualization system [13,17,23,41].…”
Section: Related Workmentioning
confidence: 99%
“…Some of the interactive functionalities available to support the decision process include inspecting the specific domain value of each attribute (e.g., the rent of home1 being equal to $500), sorting the alternatives with 1 Video demo: www.cs.ubc.ca/group/iui/VALUECHARTS respect to a specific attribute, swapping attribute columns, and resizing the width of an attribute's column to see how that would impact the decision outcome. For the ValueChart user study (fully described in [17]), 95 participants were recruited (ages 16 to 40) to perform 5 different types of visualization tasks, chosen from a set of low-level data analysis tasks defined by Amar et al [2]. These five tasks (shown in Table 1) require answering questions from different domains for preferential choice (i.e., rental homes, universities, cell phones, restaurants, and hotels) using functionalities of ValueChart (e.g., sorting, reordering, weighting attributes).…”
Section: Valuechart and User Studymentioning
confidence: 99%
See 3 more Smart Citations